Incidence, risk factors, and outcomes of warfarin-associated major bleeding in Thai population - Watcharapong Priksri (2019)
© 2019 John Wiley & Sons, Ltd. Purpose: This study aimed to describe incidence, risk factors, and outcomes of warfarin-associated major bleeding (WAMB) in Thai patients. Method: A nested case-control study was conducted in a cohort of adult patients receiving ≥6 months of warfarin therapy who were prospectively followed up at a tertiary care hospital in Thailand during January 2011 to December 2014. Logistic regression was used to identify risk factors associated with WAMB. The area under the receiver operating characteristic (AUROC) curve was used to assess the performance of the HAS-BLED score to predict WAMB in patients with non-valvular atrial fibrillation (NVAF). Results: Among 1604 patients (2972 patient-year of follow-up), there were 93 major bleeding that occurred in 76 patients. The incidence of WAMB was 3.13 events per 100 patient-year. Time in therapeutic range (TTR) of <60% (RR: 3.62, 95% CI: 1.94-6.73, P < 0.001), mechanical valve replacement at mitral position (RR 3.43, 95% CI: 1.92-6.16, P < 0.001) cancer (RR: 2.84, 95% CI: 1.11-7.29, P = 0.029), and age ≥ 65 years (RR: 2.37, 95% CI: 1.20-4.67, P = 0.012) were independent risk factors for WAMB. There were 17 fatalities and 12 cases of disabilities from WAMB. Mean cost of WAMB was 45 341.54 THB/event. An exploratory analysis suggested that HASBLED score demonstrated an excellent discriminatory capacity to predict WAMB among NVAF patients (AUROC of 0.91, 95% CI: 0.85-0.97, P < 0.001). Conclusion: WAMB in Thai population is common and associated with high rate of morbidity and mortality. Improvement in anticoagulation control is clearly needed.